The CORD (Couple Card) game in teaching the skill of oral reading ‏ ‏Seventh grade students of Government Secondary School 2 ‎Padang - Dianti Gustia ‎ Sari; Zainul Arifin (Universitas Islam Negeri Imam bonjol Padang, 2023)
This dissertation was written with the subject of